2017
DOI: 10.1371/journal.pone.0184022
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical phenotyping unravels novel metabolic abnormalities and potential biomarkers associated with treatment of GLUT1 deficiency with ketogenic diet

Abstract: Global metabolomic profiling offers novel opportunities for the discovery of biomarkers and for the elucidation of pathogenic mechanisms that might lead to the development of novel therapies. GLUT1 deficiency syndrome (GLUT1-DS) is an inborn error of metabolism due to reduced function of glucose transporter type 1. Clinical presentation of GLUT1-DS is heterogeneous and the disorder mirrors patients with epilepsy, movement disorders, or any paroxysmal events or unexplained neurological manifestation triggered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
4
24
0
1
Order By: Relevance
“…For instance, KD did not elevate cortisol in CSF, whereas it has been reported to do so in plasma; these latter studies, were, however, in rheumatoid arthritis patients [19,51]. Cappuccio et al reported elevated plasma hydroxybutyryl-and acetyl-carnitine and lower methylmalonyl-carnitine in KD-treated glucose transporter 1 deficient patients [16], similar to the present results. Also, Schoeler et al demonstrated a stronger -hydroxybutyrate response to KD treatment in patients with optimal clinical response vs. those with no response; however, they also reported that optimal responders had higher baseline CSF -hydroxybutyrate and octanoyl-and acetyl-carnitine [21].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For instance, KD did not elevate cortisol in CSF, whereas it has been reported to do so in plasma; these latter studies, were, however, in rheumatoid arthritis patients [19,51]. Cappuccio et al reported elevated plasma hydroxybutyryl-and acetyl-carnitine and lower methylmalonyl-carnitine in KD-treated glucose transporter 1 deficient patients [16], similar to the present results. Also, Schoeler et al demonstrated a stronger -hydroxybutyrate response to KD treatment in patients with optimal clinical response vs. those with no response; however, they also reported that optimal responders had higher baseline CSF -hydroxybutyrate and octanoyl-and acetyl-carnitine [21].…”
Section: Discussionsupporting
confidence: 85%
“…Clearly many systemic changes occur with dietary therapy, making it difficult to sort out key mechanisms of efficacy. To date a number of studies have examined changes in blood metabolites aside from ketone bodies and glucose, typically examining a limited number of predetermined compounds to address specific hypotheses [15][16][17][18][19][20][21]. While cerebrospinal fluid (CSF) is significantly more difficult to collect than blood, analysis of CSF metabolites may be more relevant to KD mechanisms in epilepsy [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical metabolomics testing, such as for IEM screening, is a nascent testing approach that is amenable to multiple sample types, can substitute tens of smaller assays, and represents an important proof‐of‐principle to support future pre‐clinical and clinical applications for metabolomics . Expanding on this, additional studies will provide new insights into acute and chronic diseases such as cardiovascular disease, hypertension, cancer, inflammatory disease, autoimmune disease, metabolic disorders, and neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…With the end use clearly stated, it is recommended that the 100 s of metabolites from clinical metabolomics research be filtered to a short list of 1 to 10 biomarkers for subsequent targeted analytical assay development, validation, and algorithm development described by Xia et al 13 Clinical metabolomics testing, such as for IEM screening, is a nascent testing approach that is amenable to multiple sample types, [37][38][39] can substitute tens of smaller assays, and represents an important proof-of-principle to support future pre-clinical and clinical applications for metabolomics. [37][38][39]80,84,85,88,89,95,96 Expanding on this, additional studies will provide new insights into acute and chronic diseases such as cardiovascular disease, hypertension, cancer, inflammatory disease, autoimmune disease, metabolic disorders, and neurological diseases. Genome-wide association studies can link genotypes to biochemical profiles, 97,98 and future analyses will provide increased resolution into the penetrance of the genotypes and the clinical accuracy of the biochemical profiles associated with these genetic predispositions.…”
Section: Discussionmentioning
confidence: 99%
“…Основные методы диагностики заболевания сводятся к проведению люмбальной пункции с целью определения уровня глюкозы в ликворе и молекулярно-генетическому тестированию. Специфическим маркером синдрома дефицита GLUT1 является низкая концентрация глюкозы в спинномозговой жидкости (<2 ммоль / л) [5]. Соотношение уровней глюкозы в спинномозговой жидкости и глюкозы в крови обычно составляет менее 0,4 [23].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified